Australian occupational therapists' perspectives of consumers authentically contributing to student learning during practice placements: 'It just makes sense!' but 'we need a process'. (13th November 2022) - Bevitt, Thomas; Isbel, Stephen; Pereira, Robert B.; Bacon, Rachel
Abstract: Introduction: Collaborating with consumers in designing, delivering, and evaluating curricula is an ongoing initiative within occupational therapy tertiary courses in Australia. Within the Australian educational context, consumers are involved in on‐campus educational activities. Student occupational therapists must complete 1000 hours of practice placements as part of their education. To date, no research has explored how consumers could contribute to student occupational therapists' learning during practice placements. This study aimed to explore Australian occupational therapists' perceptions of consumers providing feedback to students during practice placements. Methods: A qualitative descriptive approach was adopted to engage with the diversity of practice contexts and gain a rich dataset from the occupational therapy profession. A qualitative questionnaire was developed and distributed using snowballing techniques. The questionnaire asked recipients to reflect on the risks, challenges, and benefits of consumers providing feedback to student occupational therapists from all stakeholders' perspectives. Demographic data were collated, and reflexive thematic analysis was used to construct themes. Findings: Responses were received from 81 participants. Most respondents identified as experienced occupational therapists from metropolitan locations across Australia. Reflective thematic analysis was used to construct three themes: Personal capability of consumers and students will enable, inhibit, and be developed by engaging in a feedback process; an educator‐controlled process to ensure safety for all stakeholders is required for time‐poor practice contexts; and us versus them: Shifting control to consumers can disempower practice educators. Conclusion: Engaging with consumers throughout all aspects of student occupational therapists' educational programme is required, including practice placements. New educational initiatives need to consider all stakeholders' concerns to ensure that authentic contribution from consumers is made within the various practice contexts. A co‐design approach that involves all stakeholders to develop a feedback process may result in high‐quality learning experiences that assist students to become safer, consumer‐centred health professionals.